DEPTOR attenuates asthma progression by suppressing endoplasmic reticulum stress through SOD1 - Hao Wang; Lei Zhang; Yunxiao Shang (Biology Direct)
Abstract Endoplasmic reticulum (ER) stress has been shown to play a pivotal role in the pathogenesis of asthma. DEPTOR (DEP Domain Containing MTOR Interacting Protein) is an endogenous mTOR inhibitor that participates in various physiological processes such as cell growth, apoptosis, autophagy, and ER homeostasis. However, the role of DEPTOR in the pathogenesis of asthma is still unknown. In this study, an ovalbumin (OVA)-induced mice model and IL-13 induced 16HBE cells were used to evaluate the effect of DEPTOR on asthma. A decreased DEPTOR expression was shown in the lung tissues of OVA-mice and IL-13 induced 16HBE cells. Upregulation of DEPTOR attenuated airway goblet cell hyperplasia, inhibited mucus hypersecretion, decreased the expression of mucin MUC5AC, and suppressed the level of inflammatory factors IL-4 and IL-5, which were all induced by OVA treatment. The increased protein expression of ER stress markers GRP78, CHOP, unfolded protein response (UPR) related proteins, and apoptosis markers in OVA mice were also inhibited by DEPTOR overexpression. In IL-13 induced 16HBE cells, overexpression of DEPTOR decreased IL-4, IL-5, and MUC5AC levels, preventing ER stress response and UPR process. Furthermore, from the proteomics results, we identified that SOD1 (Cu/Zn Superoxide Dismutase 1) may be the downstream factor of DEPTOR. Similar to DEPTOR, upregulation of SOD1 alleviated asthma progression. Rescue experiments showed that SOD1 inhibition abrogates the remission effect of DEPTOR on ER stress in vitro. In conclusion, these data suggested that DEPTOR attenuates asthma progression by suppressing endoplasmic reticulum stress through SOD1.